Klasifikasi Puisi Arab Jahiliyah Menurut Ibn Qutaybah dalam Kitab al-Shi'r wa-al-Shu‘arā’ - Muyassarah; Abadi, Jaenafil (Al-Ma‘rifah, 2021)
This research discusses the classification of Arabic poem (shi‘r) of the pre-Islamic period (Jahilīyah) in the book of al-Shi‘r wa-al-Shu‘arā’ by Abū Muḥammad ‘Abdullāh ibn Muslim ibn Qutaybah. In this research, we review in simple terms the classification of poems based on the quality of lafaẓ and meaning, the quality of lafaẓ, the quality of meaning, and the quality of limited lafaẓ and meaning a literary work, especially in the poem (shi‘r) as described in the book of al-Shi‘r wa-al-Shu‘arā’. Through the poem, the Arabic poet of Jahilī expresses his feelings through the poem he creates. The theme raised in the poem is the reality or quotes that are very familiar with the life of the Arab community at that time. One of the most influential Arabic poets of Jahilī is Imru’ al-Qays. In his poetry, Imru’ al-Qays describes his feelings, both regarding love, greed, sadness, spree, and so on relating to the conditions of the Arab environment. Likewise with other poets took the theme of poetry that was inseparable from the various Arab cultures.